THE ETHOS OF MATERIALISM AND THE CHALLENGES OF THE GLOBAL RECESSION PERSPECTIVE OF THE QUR'AN SURAT AL-FAJR [89]: 15-20 - Itmam Aulia Rakhman; Miftahul Janah (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Modern humans in this global era face the problem of the meaning of life due to excessive pressure on the material aspects of life. Progress and sophistication in how to realize the desire to fulfill material life which is the main characteristic of modern times must be redeemed at a very expensive cost, namely the loss of awareness of the deeper meaning of life. Human happiness and self-esteem is in outward physical appearance based on material wealth. On another dimension, the global recession which was partly caused by an increase in global central bank rates which resulted in a prolonged decline in the economic sector, including the unemployment rate, industrial production, capital flows, etc. Of course it has an impact on each individual. The global recession as a test in the form of limitations and difficulties in obtaining sustenance needs to be anticipated so that human happiness is not limited to material life. This article will examine the ethos of modern human materialism in QS. Al-Fajr [89]:15-20 as well as the solutions offered by the mufasir (experts of the Qur'an) in dealing with the global recession which 'threats' the economy of society from the point of view of spirituality (religious soul). This article examines this interpretation using the analytical-descriptive method in an effort to present the Qur'an as a guidebook for the challenges of globalization so that it becomes a book that shows its relevance at all times and places (shalih li kulli Zaman wa Makan).